2022
DOI: 10.3390/rs14184653
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Satellite Chlorophyll-a to the Extreme Sea Surface Temperatures over the Arabian and Omani Gulf

Abstract: Extreme events such as Marine Heat Waves (MHWs) and Low Chlorophyll-a (LChl-a) in the ocean have devastating impacts on the marine environment, particularly when they occur simultaneously (i.e., the compound of MHWs and LChl-a events). In this study, we investigate the spatiotemporal variability of MHWs and LChl-a events in the Arabian and Omani Gulf. For this purpose, we used satellite-based high-resolution observations of SST (0.05° × 0.05°; from 1982 to 2020) and chlorophyll-a concentration data (0.04° × 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…By comparing the modeled time series with satellite data, it can be concluded that satellite sensors might be overestimating surface chlorophyll. The satellite observations (SeaWiFS at 24°N, 58°E from Asia-Pacific Data Research Center) from 1997 to 2013 suggested that chlorophyll-a concentration in the Gulf of Oman increased in August 2000, September 2004 and August 2008 [47]. The results showed that a significant correlation exists between inshore and offshore chlorophyll-a distribution throughout the year.…”
Section: Model Validation and Comparison With Satellite Datamentioning
confidence: 90%
See 2 more Smart Citations
“…By comparing the modeled time series with satellite data, it can be concluded that satellite sensors might be overestimating surface chlorophyll. The satellite observations (SeaWiFS at 24°N, 58°E from Asia-Pacific Data Research Center) from 1997 to 2013 suggested that chlorophyll-a concentration in the Gulf of Oman increased in August 2000, September 2004 and August 2008 [47]. The results showed that a significant correlation exists between inshore and offshore chlorophyll-a distribution throughout the year.…”
Section: Model Validation and Comparison With Satellite Datamentioning
confidence: 90%
“…Recent studies have delved into the biological and chemical parameters of the Persian Gulf and Oman Sea, employing coupled physical-biological ROMS models and satellite data to explore various facets of marine ecology [24][25][26][27][28][29]. However, there remains a gap in our understanding of the behavior of biological parameters with seasonal changes in the Oman Sea region, especially in the context of basin hydrodynamics and atmospheric forces.…”
Section: Current Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be considered as a first step to better understand that the severity of MHWs is not only directly caused by their occurrence, but also by their interactions with other atmospheric conditions that may lead to other catastrophic extreme events. Therefore, for future work, we propose to investigate the combination between MHWs and other extreme events in the region such as storms, atmospheric heatwaves, low chlorophyll-a events, and extreme nutrient and oxygen depletion events which is also suggested by (Leonard et al, 2014;Le Grix et al, 2021;Hamdeno et al, 2022). Due to the rapid increase in the frequency, days, and intensity of MHW, it is also necessary to quantify their potential impacts on the overall ecological components, structures, functioning, and overall health of the Mediterranean Sea.…”
Section: Marine Heatwaves In the Mediterranean Seamentioning
confidence: 99%
“…Previous studies have shown that these climate modes, such as ENSO, DMI, NAO, AO, and PDO, favor or suppress the occurrence of MHW-LChl events (Le Grix et al, 2021;Hamdeno et al, 2022). To further understand the influence of large-scale modes of interannual to decadal climate variability on compound MHW-LChl events in the study region, we perform correlation and composite analysis between the total days of compound events and five different climate modes (see Section 2.1).…”
Section: Relationship Between Mhw-lchl Extremes and Climate Modesmentioning
confidence: 99%